PENDIDIKAN KARAKTER ANAK USIA DINI DALAM KEGIATAN BERMAIN SENTRA - Rosita Rosita; Neneng Alawiyah; Amita Diananda (JECIES: Journal of Early Childhood Islamic Education Study, 2021)
This qualitative research was conducted with a background to enrich the discourse and paradigm regarding the pattern of Early Childhood education in character formation. In addition, researchers want to detect and see the effects of center learning on the formation of early childhood character. Although each learning pattern has an influence and has a change in students, the center's activities have a unique value in character planting. This study uses a descriptive qualitative approach using Spradley analysis. The results of the study describe the state of character education in learning centers in the Islamic Village kindergarten. That the internalization of character values is carried out through the foothold in the center from the initial conditioning to the footing after playing. Thus this research is expected to provide a positive new discourse and has the aim to provide a true understanding of what is happening around us.